Intelligent sourcing agent system - Lim, Tobias Kuo Jie (Nanyang Technological University, 2020)
This project aims to explore possible technological solution to intelligently automate processes of a Multi-National Company (MNC) to reduce resources used for manual intervention of repetitive tasks using software events that are modelled after the business events. With such automation, companies can expect to reduce cost of resources that are spent on current solutions for solving such problems. Modern technologies and techniques that enhances the product of this project will also be shared and discussed.